Guided Imagery and Music on Anxiety of Mayor Operating Inpatients of Tangerang General Hospital - Susilawati, Ela; ., Mawardi; Hendrawati, Mike Heri; Resna, Riksa Wibawa (KnE Life Sciences, 2019)
Background: The anxiety level of clients who will undergo major surgery is very inﬂuential on the smooth operation of the operation to be carried out. Actions of a nurse to overcome the anxiety that occurs on the client pre-operation are needed to be able to resolve the issue. Objective: This study aimed to look at changes in the patient’s anxiety level after guided imagery and music performed by nurses before the surgery performed. Methods: The research was used quasi-experimental with pretest-posttest control group design, sample collected used Quota Sampling method with total 38 sample divided into two group, the instrument of measuring the anxiety levelused(HARS-A)scale,whichthestatistictestusedWilcoxonSignedRankTestand Mann-Withney. Result: There was a decrease in the value of anxiety in the group given guided imagery and music with an average value of 7.50 (p-value:0.000), whereas there was a tendency to increase the value of anxiety in the control group with an average value of 6.00 (p-value:0.083). There were signiﬁcant differences in the mean value between the intervention groups (14.03) and the control group (24.97) with p-value 0.001. Conclusion: Giving stimuli in the form of guided relaxation techniques can help reduce the level of anxiety in clients who will undergo surgery because it can help clients to distract their anxiety towards the operation process to other things of beautiful nature. The addition of music as one of the image transformation media can strengthen relaxation guidance to be able to reach the maximum level of relaxation that will have an impact on the ability to reduce their anxiety level